EDUKASI MENABUNG SEJAK DINI BAGI SISWA SEKOLAH DASAR MUHAMMADIYAH WANI DUA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Nursalim; Nur Wahda Ayu Setiawati (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
Saving is an important step in forming good financial habits in children. Savings education not only teaches the value of money, but discipline, responsibility and money planning. Routine and diligent savings activities can be beneficial for life. Apart from that, saving from an early age also teaches students to be thrifty and builds students' characteristics not to waste money. This activity was carried out through stages of observation, delivery of material, discussion, and the process of making a piggy bank to become a symbol of real savings practices. Apart from providing benefits to students, this program also has the potential to create a wider positive impact in village communities, with students becoming agents of change who bring knowledge and understanding about the importance of saving to their families. This program shows that a structured and driven educational approach can be an effective tool in increasing financial literacy and preparing students to manage their finances wisely. Therefore, this program can be an inspiring model for similar efforts in other regions.